Volunteering on the rise: Generation of 1968 more active even in retirement - Luise Burkhardt; Jürgen Schupp (DIW Weekly Report, 2019)
According to representative survey results of the Socio-Economic Panel (SOEP), volunteer rates have been continually rising in Germany over the past 30 years. Contributing factors include young adults' growing willingness to volunteer as well as an increase in the volunteer behavior of older people, who begin to volunteer more often after entering retirement. A generational comparison shows that the Generation of 1968 (born between 1941 and 1954) volunteers especially frequently during retirement. Twenty-nine percent of respondents in this generation continued volunteering into retirement and 13 percent began volunteering after retiring, making the Generation of 1968 more active volunteers than older birth cohorts. Policies should support this potential resource in the future through flexible and accessible volunteer opportunities.
Keywords: C23; D64; J26; 330; Volunteering; Survey; Birth Cohort; Retirement